Detection of Porphyromonas gingivalis and Treponema denticola in chronic and aggressive periodontitis patients: A comparative polymerase chain reaction study - Ramniwas M Kumawat; Sindhu M Ganvir; Vinay K Hazarey; Asifa Qureshi; Hemant J Purohit (Wolters Kluwer Medknow Publications, 2016)
Background: The detection frequency of Porphyromonas gingivalis and Treponema denticola in chronic periodontitis (CP) and aggressive periodontitis (AgP) is not explored well in Indian population. Aim: The study was undertaken to detect P. gingivalis and T. denticola in CP as well as in AgP patients using polymerase chain reaction (PCR), and to determine the relationship between the frequency of these two microorganisms and the severity of clinical periodontal parameters. Materials and Methods: Subgingival plaque samples were collected from ninety participants (thirty CP patients, thirty AgP patients, and thirty healthy participants) and the aforementioned two microorganisms were detected using PCR. Results: However, when CP and AgP were compared for the detection frequency of two microorganisms, no statistically significant difference was noted. A statistically significant increase in the number of bacteria-positive sites increased as the score of plaque index (PI), gingival index (GI), and clinical attachment level of CP and AgP patients increased. Coexistence of P. gingivalis and T. denticola was frequently observed in deep periodontal pockets. Conclusions: Study findings suggest that P. gingivalis and T. denticola are significantly associated with the severity of periodontal tissue destruction. Statistically significant association exists between clinical periodontal parameters such as PI, GI, periodontal pocket depth (PPD), and clinical attachment loss and presence of both the microorganisms.